Editorial: e-meetings. - Lamb, Paul (Parliamentary Journal, 2009)
Part of a special issue on “e-meetings.” In an editorial, the writer discusses how this issue of the Parliamentary Journal came to be a special issue on e-meetings. He acknowledges that the concept of e-meetings remains a rather nebulous one but asserts that the information contained in this issue will be helpful for any organization that wishes to use a non-traditional meeting forum. He provides a brief overview of some of the topics addressed in this special issue.